Table of Content - - (Journal of engineering sciences and information technology, 2023)
Table of Content:1. Enhancing Coherent Optical Communication Performance Using FBG as Dispersion CompensatorEng. Raghad Mohammad Fayez Alalfi, Dr. Abdulkareem Alsalem2. The role of modern augmented applications in improving the efficiency of engineering projectsEng. Sami Abdullah Mandani, Eng. Mohammad Jasem Alfareis3. Development of a data encryption algorithm to enhance security in D2D communications by secure key exchangeEng. Essam Mohammad Asaad , Prof. Abdulkarim Assalem4. Evaluation of Bus Rapid Transit System: Riyadh city, Saudi ArabiaAhmed Mohammed Alshehri5. A GIS-Based Streets Network Analysis in Al-Riyadh District, Al-Khartoum CityDr. Sahar I. M. Abd Elrahman
Keywords: Journal of Engineering Sciences and Information Technology